Enterprise Architecture Design for the Transformation of Online Financial Services - Wedha, Bayu Yasa; Vasandani, Michael Sagar; Wedha, Alessandro Enriqco Putra Bayu (Politeknik Ganesha Medan, 2023)
In the ever-expanding digital era, online financial services have emerged as a significant component of the global financial ecosystem. Digital transformation has altered the operations and consumer interactions of financial services companies. By implementing Enterprise Architecture design, financial services companies can adapt, flourish, and compete in an increasingly competitive environment. This article examines the essential function of Enterprise Architecture in the evolution of online financial services. We explore how Enterprise Architecture provides a strategic framework for driving change and innovation in financial organizations. We examine the primary elements of an Enterprise Architecture, such as the business model, technology infrastructure, and data. Then, we investigate how Enterprise Architecture improves operational efficiency and decreases risk in digital financial services. In addition, the significance of security and conformance in Enterprise Architecture for online financial services is examined. Enterprise Architecture is crucial in integrating security solutions and ensuring regulatory compliance in light of rising cybersecurity threats, strict regulatory compliance, and consumer demands for data privacy. We discuss how Enterprise Architecture facilitates improved consumer experiences in online financial services. By designing solutions with the consumer in mind, businesses can meet customer expectations, increase customer retention, and build a sustainable market share. Enterprise Architecture has become an indispensable instrument for successfully transforming online financial services. Through strategic planning, technology integration, data management, and a focus on security and customer experience, financial institutions can meet the challenges and seize the opportunities presented by the digital era.